PECULIARITIES OF APPLICATION OF PSYCHOREGULATION IN THE PSYCHOLOGICAL SERVICE OF YOUNG CHESS PLAYERS - Stepanyan , A. G.; Geghamyan , V. Kh.; Sofyan, T. Sh. (Modern Psychology, 2019)
The article discusses current issues of growing interest in a chess game. Chess enables young people to realize themselves in competitions at the level of mental activity. The results of a survey of highly qualified chess players have confirmed the need to expand knowledge on the problem of psychological preparation and the introduction of methods of psychoregulation at an early stage of preparing high-level chess players.
Keywords: chess; training bones; training psychologies, psychoregulation; selfsuggestion. self-inspiration.